The Influence of Teacher Competency and Educational Infrastructure on the Quality of Junior High School Education: Teacher Competence - Limbong, Mesta; Guiron, Samuel B. (International Journal of Educational Management and Innovation, 2025)
The research was conducted to answer whether teacher competency and educational facilities significantly impact the quality of education in public junior high schools in North Cikarang. The method used in this study is a quantitative approach with a survey method. The research was conducted at public junior high schools in North Cikarang from February to May 2024, with a sample size of 72 individuals selected through purposive sampling. This study used a questionnaire instrument with a Likert scale and simple linear regression analysis. The results showed a positive and significant effect of teacher competency (X1) on the quality of education (Y) by 17 people (around 23% from sample), a positive and significant effect of educational facilities (X2) on the quality of education (Y) by 16 people (around 21.5% from sample), and a significant simultaneous effect of teacher competency (X1) and educational facilities (X2) on the quality of education (Y), with the combined effect strengthening to 23 people (around 32.1% from sample). We can also find that teacher competency and the available infrastructure, which maximizes its contribution again because of the significant influence it provides, can still be improved. Based on these results, the author suggests that schools should continue to improve teacher competency as there is still considerable room for a positive impact on the quality of education. Schools should also examine other factors that may influence the quality of education for further study.